1980
DOI: 10.1002/eji.1830100105
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of regulatory T cell circuits by immunoglobulin‐dependent structures on activated B cells

Abstract: An immunoregulatory circuit is described in which B cell blasts activate syngeneic Ly-1+2-3- T cells to (a) start a reaction which is indistinguishable from a graft-vs.-host reaction (syngeneic GvH) and (b) induce suppressor cell activity which abrogates the syngeneic GvH. Since capping the surface immunoglobulin (Ig) on B cell blasts blocks their ability to activate the circuit, it is likely that the relevant cell surface structure "seen" on the B cell by the Ly-1 T cell is either Ig itself or another molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…This perturbation of the "steady-state'' could be an antigenic stimulus for suppressor cells recognizing the expanded set of Id, whose activation would result in a control of B cell clonal expansion. This hypothetical series of events has, in fact, recently been confirmed concerning the activation of Id helper T cells [41] and antigen-specific suppressor cells [42].…”
Section: Discussionmentioning
confidence: 92%
“…This perturbation of the "steady-state'' could be an antigenic stimulus for suppressor cells recognizing the expanded set of Id, whose activation would result in a control of B cell clonal expansion. This hypothetical series of events has, in fact, recently been confirmed concerning the activation of Id helper T cells [41] and antigen-specific suppressor cells [42].…”
Section: Discussionmentioning
confidence: 92%
“…There, it was found that the i.v. injection of syngeneic B cell blasts, but not T cell blasts, into normal mice resulted in the activation of Lytl T cells which produced a GvH or HvG reaction in syngeneic recipient mice [15]. We found T cell-mediated in vivo responses to transferred syngeneic T and B cell blasts with identical numbers of injected blast-response relationship and identical kinetics [9].…”
Section: Discussionmentioning
confidence: 84%
“…It is possible that T cells in the normal spleen cell population interact with the antigenspecific immune spleen cells to generate idiotype-specific suppressor T cells (21). It is known that Ig-associated structures on activated B cells can trigger Ly-1+2 -inducer cells to stimulate Ly-2 ÷ T suppressor activity (22). Mechanisms such as these could explain how the removal of T cells from the normal spleen cell population can decrease suppression.…”
Section: Discussionmentioning
confidence: 99%